Access and utilisation of leprosy healthcare services in high-burden districts in Ethiopia - Solomon S. Marrye; Simangele Shakwane (Southern African Journal of Infectious Diseases)
Background: A lack of awareness, poor quality of care, and gender inequalities are factors associated with access and utilisation of leprosy services.